Local sympathetic nerve depletion does not alter vitiligo progression in a mouse model - Hu, Zhichao; Chen, Ting; Chen, Daoming (Frontiers in Medicine, 2025)
Vitiligo, an autoimmune skin disorder characterized by melanocyte loss, has long been associated with sympathetic nervous system activity. Clinical observations have suggested links between psychological stress, sympathetic activation, and vitiligo progression. However, direct experimental evidence for the role of sympathetic nerves in vitiligo development has been lacking. Herein, we employed 6-hydroxydopamine (6-OHDA) to induce sympathetic nerve depletion in mice before vitiligo induction. Sympathetic nerve ablation was confirmed through immunofluorescent staining of tyrosine hydroxylase. Vitiligo progression was assessed by quantifying epidermal melanocytes and CD8+ T cells using whole-mount immunofluorescence staining. The loss of melanocytes and infiltration of CD8+ T cells in vitiligo lesions were comparable between sympathectomized and control mice. Overall, our study suggested that previously observed associations between sympathetic nervous system activity and vitiligo may be concomitant effects rather than causative factors, challenging long-held clinical hypotheses.